Women, Political Struggles and Gender Equality in South Asia - Alston, M.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
A brutal gang-rape of a young woman in India in 2012 caused a global outcry against rising brutal violence against women. In response to the young woman's death and the protests that followed, the contributors analyze the position of women in South Asia, the issue of violence, women's political activism and gender inequalities.
Keywords: Ethnology$1 (BAsia.s; Economic development; Social change; Sociology; Political science; Political communication; Asian Culture; Development and Social Change; Gender Studies; Political Science; Political Communication; Sociology, general